Well Log Analysis of Nahr Umr, Shuaiba and Zubair Formations in EB-4 well of East Baghdad Oil Field, Iraq, using Rock Physics Templates (RPTs) - Ahmed S. Al-Banna; Mustafa A. Al-Khafaji (Iraqi Journal of Science, 2021)
RPT is a method used for classifying various lithologies and fluids from data of well logging or seismic inversion. Three Formations (Nahr Umr, Shuaiba, and Zubair Formations) were selected in the East Baghdad Oil field within well EB-4 to test the possibility of using this method. First, the interpretations of the well log and Density – Neutron cross plot were used for lithology identification, which showed that Nahr Umr and Zubair formations consist mainly of sandstone and shale, while the Shuaiba Formation consists of carbonate (dolomite and limestone). The study was also able to distinguish between the locations of hydrocarbon reservoirs using RPT. Finally, a polynomial equation was generated from the cross plot domain (AI versus Vp/Vs) to estimate one parameter from the other in these formations, and vice versa.